Estudo de intera????es hiperfinas em compostos intermet??licos Gd(Ni, Pd, Cu)In, Tb(Ni, Pd)In, Dy(Ni, Pd)In e Ho(Ni, Pd)In - LAPOLLI, ANDRE L. (2006)
Made available in DSpace on 2014-10-09T12:51:12Z (GMT). No. of bitstreams: 0